The Long-term Outcome of Early Spine Fusion for Scoliosis in Children With Cerebral Palsy. Issue 8 (October 2016) - Sitoula, Prakash; Holmes, Laurens; Sees, Julieanne; Rogers, Kenneth; Dabney, Kirk; Miller, Freeman
Abstract : Study Design: Retrospective review of radiographs and charts (case-only). Objective: The aim of this study was to describe the long-term outcomes of spine fusion for neuromuscular scoliosis in children below 10 years of age with cerebral palsy (CP). Summary of Background Data: Severely involved children with CP may develop early-onset scoliosis. The outcome of spine fusion is not clear and there are no studies focused on spine fusion in this young patient population. Methods: This is a retrospective review of 33 children who underwent spine fusion with unit-rod instrumentation between 1989 and 2006 for CP neuromuscular scoliosis, aged below 10 years at spine fusion, and with follow-up >5 years. Demographic, medical, and radiographic data were retrospectively assessed. Repeated measure analysis of variance and Kaplan-Meier survival estimates were used for data assessment. Results: Thirty-three of 42 patients who underwent spine fusion in this period, 19 boys and 14 girls, met the inclusion criteria. Of 9 patients who were excluded, 3 were lost to follow-up and remaining 6 died within 5 years of surgery. Mean age at surgery was 8.3 years (range, 4.4–9.9 y). Mean follow-up was 9.8 years (range, 5.5–15.8 y). Gross motor function classification system level was V in 31 patients and IV in 2 patients. Thirty-one patients (94%) had seizure disorder, 29 patients (88%) had gastric feeding tubes, and 9 patients (27%) had tracheostomy tubes. Eighty-five percent of the patients had posterior-only surgery. Mean Cobb angles preoperative, immediately postoperative, and at final follow-up were 85, 21, and 24 degrees, respectively. Mean postoperative pelvic obliquity correction was 15±9 degrees ( P <0.001). At final follow-up, there was no significant change from the postoperative measurements. Complications included 1 deep wound infection and 10 other problems. Eleven patients (28.2%) died after a mean follow-up of 5.6±3.8 years. Conclusions: In our cohort with early-onset neuromuscular scoliosis, spine fusion was associated with minimal short-term and long-term morbidity, but there was 28% mortality at 10 years of follow-up and 50% predicted mortality at 15 years.